Climatic conditions of the development of the Vlach law settlements in the western Carpathians at the turn of the 15th and 16th century on the example of the Podtatrze (Sub-Tatra) region - Kłapyta, Piotr (Balcanica Posnaniensia. Acta et studia, 2021)
Historical documents concerning many localities existing from the 14th century in the Polish and Slovak Podtatrze (Sub-Tatra) region testify the settlement crisis at the end of the 15th century, consisting in disappearance of a large number of agricultural settlements under German law and renewing them at the beginning of the 16th century under the Vlach law by the new settlers of Russniak-Vlach origin. The analysis of the record of environmental changes during this period, recorded in a number of sediment sites of lakes and peat bogs in the Tatra Mountains area, indicates that the crisis of agricultural settlement at the end of the 15th century may have been caused by long-term climate changes during the Little Ice Age. The climate crisis of the turn of the 15th / 16th century was conditioned by cooling (Spörer's solar minimum), which was overlapped with a clear regional phase of climate dampness and extreme hydrometeorological events, well reflected in the sedimentological record in the Tatra Mountains. The demographic crisis resulted in the depopulation of a large part of the eastern Podtatrze and resulted in the need to change the economic strategy in the mountainous Carpathian areas from agriculture to pastoral/agricultural activity based on innovative regulations of the Vlach law. The new communities managed to adapt to the unfavorable environmental conditions, and the villages under the Vlach law functioned in this area in the following centuries without any problems based on the pastoral and agricultural economy, despite the still unfavorable climatic conditions of the Little Ice Age.